ANALYSIS OF MICROPLASTIC CONTENT IN SEAWATER AT PADANG AND PARIAMAN TOURISM BEACHES, WEST SUMATRA PROVINCE - Fikri, Ishlahul; Nedi, Syahril; Elizal, Elizal (Asian Journal of Aquatic Sciences, 2022)
Coastal and marine areas have the potential for anthropogenic pollution. Solid waste, especially plastic, is a pollutant that contributes greatly to polluting coastal areas. Plastic will degrade into small sizes known as microplastics. The purpose of this study was to determine the content of microplastics in the Padang and Pariaman Coastal Waters, West Sumatra. This research was conducted in November 2021 in the seawaters of Padang Wisata Beach (Air Manis Beach and Muaro Lasak Beach) and Pariaman Beach (Kata Beach and Gandoriah Beach) of West Sumatra Province. Based on the results of the study, four types of microplastics were found, namely fiber, film, fragments, and granules. The type of fragment is the dominant type found, followed by the type of film, fiber and granules. Microplastic abundance at Air Manis Beach ranged from 616.67-2196.97 particles/m3, Muaro Lasak Beach 916.67-2396.67 particles/m3, Kata Beach 320.00-1190.00 particles/m3, and Gandoriah Beach 550, 00-1363.33 particles/m3. In general, at Padang Beach and Pariaman Beach by type, microplastic fragments were the most common type found with a percentage of 53%. The type of film is the second most common type (32%), followed by the type of fiber (11%) and the type of grain (4%). Microplastics were distributed in seawater at Padang Beach and Pariaman Beach with different abundances.